A new simple score of chronic cough: cough evaluation test - Zhan, Wenzhi (BMC Pulm Med, 2020)
BACKGROUND: Chronic cough has an important impact on physical, social and psychological aspects. A simple and effective method to assess different aspects of chronic cough severity is required. We aimed to develop a simple, self-completed test, Cough Evaluation Test (CET), to evaluate cough severity and its impact on health. METHOD: The items of preliminary CET were generated based on literature review and clinical practice. Items reduction was conducted by modified Delphi method. Patients with chronic cough were recruited to complete CET, Cough Visual Analog Scales (VAS), Mandarin Chinese version of the Leicester Cough Questionnaire (LCQ-MC), and Cough Symptom Score (CSS). Reassessments were performed at 1 week apart before treatment, and after more than 2 weeks treatments. Concurrent validation, internal consistency, repeatability, responsiveness and the minimal important difference (MID) were determined. RESULTS: CET consists of five items with a 5-point Likert scale (1–5 scaling of items, 5–25 score range). The Cronbach’s alpha values for CET was 0.80. CET showed a stronger correlation with LCQ-MC (r = − 0.74) compared to that between LCQ-MC with VAS (r = − 0.61). CET also showed a stronger correlation with VAS (r = 0.70) compared to that between VAS with other measures. Intraclass correlation coefficients for CET was 0.84. In patients undergoing treatment, CET scores significantly changed (p < 0.0001). The MID of CET was 2. CONCLUSION: Cough Evaluate Test is a reliable, valid and responsive tool to simply evaluate impact of cough on physical, social and psychological aspects.